A comparative study of needle stick injury incidence, safety practices, and impact between doctors and nurses at tertiary care hospitals in Peshawar - Hamza, Muhammad; Ahmed, Daniyal; Amin, Iqra; Wazir, Fouzia; Tahir, Alishba; Bilal, Janeeta; Kawish , Muhammad Talha; Jahan, Sarwat (International Journal of Pathology, 2026)
Background: Needle Stick Injuries (NSIs) increase the risk of blood-borne disease among healthcare workers due to frequent, accidental exposure to sharp instruments during patient care, leading to physical and psychological consequences. We intend to compare the incidence, knowledge, attitude, practice, and impact of needle stick injuries among doctors and nurses in tertiary care hospitals in Peshawar, Pakistan.Methods: A cross-sectional study was conducted from March to August 2025 in public and private tertiary care hospitals in Peshawar, involving 400 healthcare workers through a stratified convenience sampling technique. A pre-tested, self-structured questionnaire assessed the incidence, knowledge, attitudes, practices, and impacts of needle stick injuries among doctors and nurses. SPSS version 27 was used for analysis, with chi-square tests comparing groups(p<0.005).Results: Among 400 healthcare workers in Peshawar tertiary hospitals, 73.5% of the participants reported NSIs, significantly higher in nurses (79.5%) than doctors (67.5%) (p < 0.005). Only 37.5% showed good knowledge (p = 0.018 between professions). Moderate concern was reported by 77%, with no significant difference by profession (p=0.434). Registered nurses and interns were perceived as the highest-risk groups (P < 0.001), especially in private hospitals (P < 0.001). Safe practices were followed by 52%, with nurses showing better adherence (p=0.003). NSIs caused physical pain (57.8%), psychological distress (45.3%), and impacted work behaviour (78%). Non-reporting occurred in 42.8% of cases, mainly due to minor injury perception (37.8%) or lack of reporting awareness (16.8%).Conclusion: Needle stick injuries are prevalent, particularly among healthcare workers, driven by procedural exposure and unsafe practices. Although knowledge and attitudes are similar in doctors and nurses, nurses exhibit safer practices due to better training. Interventions to reduce the incidence should focus on mandatory training, no-recapping policies, improved reporting, and safety devices to reduce NSI incidence and impacts, especially in public hospitals